2021
DOI: 10.48550/arxiv.2103.03252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constraining the Epoch of Reionization With Highly Dispersed Fast Radio Bursts

Michael Pagano,
Hannah Fronenberg

Abstract: The period in which hydrogen in the intergalactic medium (IGM) is ionized, known as the Epoch of Reionization (EoR) is still poorly understood. The timing and duration of the EoR is expected to be governed by the underlying astrophysics. Furthermore, most models of reionization predict a correlation between the density and ionization field. Here we consider using the mean dispersion measure (DM) of high redshift Fast Radio Bursts (FRBs) as a probe of the underlying astrophysics and morphology of the EoR. To do… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Since the DM is a noisy distance estimate, FRBs with known host can be used to compile a DM -redshift relation. This turns FRBs into standardisable radio transmitters, which can be used to probe the baryon content of the Universe at late times (Walters et al 2019;Macquart et al 2020), the ionisation history of the IGM (Jaroszynski 2019;Bhattacharya et al 2020;Pagano & Fronenberg 2021) or the current expansion rate (Wu et al 2020).…”
mentioning
confidence: 99%
“…Since the DM is a noisy distance estimate, FRBs with known host can be used to compile a DM -redshift relation. This turns FRBs into standardisable radio transmitters, which can be used to probe the baryon content of the Universe at late times (Walters et al 2019;Macquart et al 2020), the ionisation history of the IGM (Jaroszynski 2019;Bhattacharya et al 2020;Pagano & Fronenberg 2021) or the current expansion rate (Wu et al 2020).…”
mentioning
confidence: 99%
“…Qiang et al [44] showed that FRBs can be used to test the possible cosmic anisotropy. Pagano & Fronenberg [45] pointed out that the highly dispersed FRBs can be used to constrain the epoch of cosmic reionization. Pearson et al [46] showed that strongly lensed repeating FRBs can be used as the probes to search for gravitational waves.…”
Section: Introductionmentioning
confidence: 99%
“…Second, high-redshift FRBs are expected to be sensitive cosmological probes. Theoretical predictions show that a population of FRBs at 𝑧 ∼ 3 βˆ’ 4 could be used to probe second helium reionization happening around redshift 𝑧 β‰ˆ 3.5 [56][57][58][59][60], while signals from 𝑧 > 5 would primarily trace variation in the ionization state of hydrogen atoms, and, consequently, could be used to probe the Epoch of Reionization [EoR,12,[61][62][63][64][65]. Such measurements would help to constrain the total optical depth of the Cosmic Microwave Background (CMB), 𝜏, to a higher accuracy than what is presently achievable [12,[61][62][63].…”
Section: Introduction a New Type Of Radio Transient Signals Calledmentioning
confidence: 99%
“…Although the importance of high-redshift FRBs as the EoR probes has been praised in literature [12,[62][63][64][65], existing works make assumptions that either lead to biases in the results or limit the constraining power of the data. Fialkov & Loeb [12] were the first to point out that FRBs could be used as precision probes of the EoR and performed a simplified error analysis to estimate the expected accuracy on 𝜏 (a similar analysis was performed by Beniamini et al [62]), which stimulated further studies.…”
Section: Introduction a New Type Of Radio Transient Signals Calledmentioning
confidence: 99%
See 1 more Smart Citation